Pengembangan Kreativitas Mahasiswa Melalui Pelatihan Pemanfaatan Botol Bekas sebagai Kerajinan Vas Bunga Bernilai Ekonomis - Muhammad Juwantho Lewa; Murni Nia; Abdul Rahman; Nur Hayun; Abdul Jarlin; Sudarsi Sudarsi; Efa Efa; Desi Desi; Sinar Maharani (Indonesia Berdampak: Jurnal Pengabdian kepada Masyarakat, 2026)
Plastic waste, particularly used plastic bottles, has become one of the environmental issues that requires productive and sustainable solutions. This community service activity aimed to enhance students' creativity through training on transforming used plastic bottles into flower vase crafts with economic value. The method employed was project-based learning, which actively involved participants in every stage of the production process, including material preparation, bottle cutting, bottle assembly, yarn wrapping, and finishing. Data were collected through observation and documentation during the implementation of the activity. The results showed that participants were able to create various attractive and creative flower vase designs according to their individual ideas and creativity. In addition, the activity improved participants’ understanding of plastic waste management, handicraft-making skills, and awareness of the importance of recycling in daily life. The products produced possess functional, aesthetic, and economic values and have the potential to be developed into creative business products with relatively low production costs. Therefore, training on the utilization of used plastic bottles as flower vase crafts can serve as an effective alternative activity to foster students' creativity while supporting environmental conservation efforts and the development of the creative economy.